The Minkowski Property and Reflexivity of Marked Poset Polytopes - Fang, Xin; Fourier, Ghislain; Pegel, Christoph (The Electronic Journal of Combinatorics, 2020)
We study the Minkowski property and reflexivity of marked poset polytopes. Both are relevant to the study of toric varieties associated to marked poset polytopes: the Minkowski property can be used to obtain generators of coordinate rings, while reflexive polytopes correspond to Gorenstein–Fano toric varieties.